About the type species of the subgenus Scelolethrus Semenov, 1892 of the genus Lethrus Scopoli, 1777 (Coleoptera: Geotrupidae: Lethrinae) - G.V. Nikolajev (Кавказский энтомологический бюллетень, 2016)
Lethrus spinimanus Jakovlev, 1892 is designated as the type species of the subgenus Scelolethrus Semenov, 1892 of the genus Lethrus Scopoli, 1777 according to the article 67.2 of International Code of Zoological Nomenclature. This is one of the three species included in the composition of the subgenus in its original description